Applications of SSNMR to new materials - Knight, Lyndsey (2017)
The domain sizes of a range of diblock polymers have been measured using solid-state NMR spin diffusion experiments carried out under fast magic angle spinning (MAS). 1H-1H exchange spectra were acquired at a range of mixing times and the results displayed effects due to both intra-domain and inter-domain spin diffusion. By fitting the data to an initial rate approximation domain sizes and spin diffusion coefficients were calculated. Simulations were also carried out to determine the impact of T1 relaxation during the experimental mixing time.